VARIASI METODE CHEBYSHEV DENGAN ORDE KEKONVERGENAN OPTIMAL UNTUK MENYELESAIKAN PERSAMAAN NONLINEAR - Julia Murni; Imran M.; Sigit Sugiarto (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
This article discusses variants of Chebyshev's methods to solve a nonlinear equation. Analytically, it is shown that the methods are of four order. Numerical comparisons show that the proposed methods are better than Newton's method, Chebyshev's method, Chebyshev-Halley's method, and Jarratt's method in performance, in terms of succeeding in obtaining the root.